Comparison of Rapid Antigen Test with RT-PCR for COVID-19 Diagnosis: Performance and Limitation - Ali Ahsan; Chaudhry Ahmed Shabbir; Muhammad Abdul Qadeer; Aleeha Rafiq; Adnan Yaseen; Mohammad Shaokat Ali; Ishtiaq Ahmad (Russian Open Medical Journal)
The COVID-19 pandemic has profoundly impacted healthcare systems worldwide, necessitating the development of rapid and accurate diagnostic tools. The study aimed to compare the performance of a Rapid Antigen Test (RAK) with reverse transcription polymerase chain reaction (RT-PCR) for COVID-19 diagnosis, considering its global usage, promising data, and the convenience of using saliva samples. Methods — A cross-sectional, single-blinded study was conducted in Lahore, Pakistan, using 7,580 samples collected between May 2021 and June 2022. Three hundred twenty samples were tested with RAK and RT-PCR using logistic regression analysis to look at sensitivity, specificity, and accuracy and whether there was a link between RAK results and RT-PCR cycle threshold values. Results — Overall, the RAK demonstrated 67% sensitivity and 75% specificity. Likelihood ratios were 2.71 (positive) and 0.43 (negative). The disease prevalence was 70.00%. PPV and NPV were 86.36% and 50.00%, respectively. Logistic regression showed a significant association between RAK results and RT-PCR CT values (odds ratio=6.333). Kit sensitivity varied by viral load: 100% at CT≤20, 63% at CT 21-25, and 22% at CT>26. Conclusion — This study would provide an insight to the work efficiency of commercially used rapid antigen based COVID-19 screening kit.